The Urgency of Artificial Intelligence Criminal Responsibility as Cybercriminals - Cheny Berlian; Helmi; Hafrida (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of information technology at this time has created many changes in life in society, the presence of artificial intelligence (A.I) in the midst of human life activities has provided many benefits both in aspects, so that today's society is very dependent on A.I which is considered very helpful in its work. Of course it can be seen that A.I also does the same thing as humans and has a positive impact and a negative impact on human life, where every aspect has a great impact on human life. The formulation of the problem in this study is the regulation of the use of artificial intelligence in Indonesia at this time and the Urgency of Criminal Responsibility of Artificial Intelligence as Perpetrators of Cybercrime. This research belongs to the normative legal research type. and the nature of this research is descriptive analysis. The results of the discussion in this study found that the A.I Regulation at this time is not specifically regulated by the law on A.I, but is regulated in the ITE law, namely in article 1 number 8 concerning electronic agents, where electronic agents are interpreted as A.I by analogy with the meaning of the word